Platelet-mediated transformation of mtDNA-less human cells: Analysis of phenotypic variability among clones from normal individuals-and complementation behavior of the tRNA[sup Lys] mutation causing myoclonic epilepsy and ragged red fibers - Chomyn, A.; Lai, S.T.; Shakeley, R.; Attardi, G.; Bresolin, N.; Scarlato, G. (American journal of human genetics, 1994)
In the present work, the authors demonstrate the possibility of using human blood platelets as mitochondrial donors for the repopulation of mtDNA-less ([rho][sup o]) cells. The noninvasive nature of platelet isolation, combined with the prolonged viability of platelet mitochondria and the simplicity and efficiency of the mitochondria-transfer procedure, has substantially increased the applicability of the [rho][sup o] cell transformation approach for mitochondrial genetic analysis and for the study of mtDNA-linked diseases. This approach has been applied to platelets from several normal human individuals and one individual affected by the myoclonic-epilepsy-and-ragged-red-fibers (MERRF) encephalomyopathy. A certain variability in respiratory capacity was observed among the platelet-derived [rho][sup o] cell transformants from a given normal subject, and it was shown to be unrelated to their mtDNA content. The results of sequential transfer of mitochondria from selected transformants into a [rho][sup o] cell line different from the first [rho][sup o] acceptor strongly suggest that this variability reflected, at least in part, differences in nuclear gene content and/or activity among the original recipient cells. A much greater variability in respiratory capacity was observed among the transformants derived from the MERRF patient and was found to be related to the presence and amount of the mitochondrial tRNA[sup Lys] mutation associated with the MERRF syndrome. An analysis of the relationship between proportion of mtDNA carrying the MERRF mutation and degree of respiratory activity in various transformations derived from the MERRF patient revealed an unusual complementation behavior of the tRNA[sup Lys] mutation, possibly reflecting the distribution of mutant mtDNA among the platelet mitochondria. 29 refs., 4 figs., 1 tab.